PLURALISME AGAMA: TELAAH KRITIS ATAS PEMIKIRAN IBN HAZM 384-456 H/994-1064 M - Syufa’at Syufa’at (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
In this global era, pluralism and multi cultures are challenge faced by ulama and intellectuals. The point ofpluralism in religiousity is to be sure of the rightness of ourselves as well as trying to understand, respect, and accept therightness of other people. The difference of religious belief needn’t make us avoid theological and spiritual relationship. Areligion should be humanistic. Ibn Hazm, an ulama and theologist who cares with pluralism, asks Muslims to apply al Qur’anand as Sunnah in facing the challenge of the 21stcentury creatively without ignoring the principle of lakum dinukum waliya aldin